IMPLEMENTASI STRATEGI PEMBELAJARAN METODE DEMONSTRASI DALAM PEMBELAJARAN FIQIH MATERI SHALAT JENAZAH KELAS X DI MAN 2 DELI SERDANG - Tasya Ramadhani; Fadhlan Wafi Lubis; Arlina Arlina (Yayasan Haiah Nusratul Islam, 2026)
Teaching fiqh on the subject of funeral prayers requires both theoretical understanding and practical skills. However, the dominant use of lectures often makes students less active and difficult to understand the correct procedures for performing funeral prayers. This study aims to describe the application of the demonstration method and analyze its effectiveness in improving students' understanding and practical skills in funeral prayer in grade X at MAN 2 Deli Serdang. This study uses a qualitative method with a phenomenological approach, with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the demonstration method is capable of creating more interactive and concrete learning, as well as improving students' cognitive, psychomotor, and affective aspects. Although there are obstacles such as time constraints and a lack of confidence among some students, these obstacles can be overcome through effective classroom management and teacher guidance. Thus, the demonstration method is considered effective for application in fiqh learning, especially for practical material.